Keanekaragaman Serangga Air di Sawah Konvensional dan Organik di Kota Padang - Hamid, Hasmiandy; Martinius, Martinius (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2017)
Study on diversity of aquatic insects in rice is important to determine the condition of the rice fields. The purpose of this research was to study the community of aquatic insects in two difference cultivations (organic and conventional) and sub districts (Koto Tangah dan Pauh) in Padang City. Purposive random sampling method was used. Samples were collected by using water insect nets and water bottle traps. The results showed that the aquatic insects found in the study site consisted of 5 orders (Coleoptera, Diptera, Ephemeroptera, Hemiptera, Odonata), 16 families, 51 species and 3808 individuals. Aquatic insect populations in organic farming was higher (5 orders, 15 families, 48 species and 3089 individuals) than conventional (4 orders, 9 families, 20 species and 719 individuals). Aquatic insects found were acting as predators (3718 individuals), detrivors (7 individuals), and omnivors (83 individuals). The diversity indexes of aquatic insects on two locations were classified as medium but the diversity in organic cultivation was higher than conventional.